“Doing Things Together Is What It’s About”: An Interpretative Phenomenological Analysis of the Experience of Group Therapeutic Songwriting From the Perspectives of People With Dementia and Their Family Caregivers - Clark, Imogen N.; Baker, Felicity A.; Tamplin, Jeanette; Lee, Young-Eun C.; Cotton, Alice; Stretton-Smith, Phoebe A. (Frontiers in Psychology, 2021)
Background: The wellbeing of people living with dementia and their family caregivers may be impacted by stigma, changing roles, and limited access to meaningful opportunities as a dyad. Group therapeutic songwriting (TSW) and qualitative interviews have been utilized in music therapy research to promote the voices of people with dementia and family caregivers participating in separate songwriting groups but not together as dyads. Procedures: This study aimed to explore how ten people with dementia/family caregiver dyads experienced a 6-week group TSW program. Dyads participated in homogenous TSW groups involving 2-4 dyads who were either living together in the community (2 spousal groups) or living separately because the person with dementia resided in a care home (1 family group, 1 spousal group). The TSW program, informed by personhood, couplehood, family-centred and group process frameworks, involved creating original lyrics through song parody and song collage. Qualified Music Therapists facilitated sessions and interviewed each dyad separately. Interviews were analysed using interpretative phenomenological analysis. Findings: Five recurrent group themes were developed, indicating group TSW: 1) was a positive shared experience, benefitting both members of the dyad and motivating further engagement with music; 2) stimulated mental processes and reignited participants’ interests and skills; 3) provided meaningful opportunities for reflection and connection with memories and life experiences; and 4) prompted interaction and collaboration, leading to social connections, empathic relationships and experiences of inclusion. Participants also highlighted how: 5) the facilitated process supported engagement, highlighting abilities and challenging doubts. Conclusions: Dyads identified group TSW as an opportunity to recognise strengths, voice ideas and opinions, share meaningful experiences, and do ‘more with music’. Participants valued TSW as a new, creative and stimulating experience that enabled connection with self and others and led to feelings of pride and achievement. Our findings further recognise how therapeutic intention and approach were reflected in participants’ engagement and responses regardless of dementia stage and type, dyad relationship, or musical background. This research may broaden perspectives and expand understanding about how people with dementia and their family caregivers access and engage in music therapy.